Aid and authoritarianism in Africa : development without democracy - Hagmann, Tobias; Reyntjens, Flip (Africa now (Zed Books)., 2016)
"In 2013 almost half of Africa's top aid recipients were ruled by authoritarian regimes. While the West may claim to promote democracy and human rights, in practice major bilateral and international donors have seen their aid policies become ever more entangled with the survival of their authoritarian protégés. This book raises an urgent and too often neglected question: to what extent are foreign aid programmes actually perpetuating authoritarian rule?" --